The Role of Bank Indonesia’s Public Relations Department in Publishing Information Regarding The Exchange of New Banknote During Ramadan - Fitriyani; Siti Khumayah; Dedet Erawati (Indonesian Journal Publisher, 2026)
The purpose of the study was to find out the role of BI’s PR office in Cirebon in distributing information related to exchanging new banknotes during Ramadan, the strategy and media used, and the obstacles faced in the information dissemination process. Data were collected using the methods of interview, observation, and document review based on qualitative analysis. Results obtained from research showed that BI's Cirebon PR office had played their roles in providing information dissemination and educating the general community about the provision of currency exchange service via the PINTAR application by applying diverse forms of communication media, including digital and non-digital one where Instagram becomes the main channel used in disseminating information. However, there are some factors affecting the effectiveness of the information distribution process which includes disparities in digital literacies level, access to information media, and technical issues (data quota limit and service queues). In addition, the demands of the people to conduct currency exchange during Ramadan season also contribute to the utilization rate of this service being very high. Therefore, it can conclude that the role of BI's PR office in Cirebon city in spreading information regarding new currency exchange has been effective, yet there remain opportunities for improvement especially in terms of guaranteeing an equitable distribution of information, improving effectiveness of communication strategies, and innovation of media utilization in conducting information dissemination and outreach activities.